Intellectual capital disclosure in public university and the determinants - Mawa, Afifah; Doddy Setiawan (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
The factors influencing Intellectual Capital Disclosure (ICD) are presented on the official websites of public universities in Indonesia. This study sought to examine ICD across 48 universities classified as PTN-BH and PTN-BLU, employing multiple linear regression analysis. The findings revealed that university internationalization, location, and complexity positively and significantly impacted ICD, whereas the presence of female rectors had no discernible effect. Furthermore, a T-test analysis indicated a significant disparity in ICD between public universities situated in Java and those outside Java. Concerning the limitation of the research, the sample used could be developed by adding other types of universities. In this context, the results described the condition of universities and future research could analyze ICD through other mass media since the analysis is not limited to the official website.